Effects of bovine leucosis virus (BLV) infection on the bovine viral diarrhoea virus (BVDV) and bovine herpes virus 1 (BHV1) seroprevalences in dairy herds in Turkey - Bilge-Dagalp, S.; Can-Sahna, K.; Yildirm, Y.; Karaoglu, T.; Alkan, F.; Burgu, I. (Ecole Nationale Veterinaire Toulouse, 2008)
In the present study, serum samples of 1984 milking cows stemming from 6 dairy herds located in various regions of Turkey were screened for neutralizing antibodies against BHV1 and BVDV using serum neutralization technique and for antibodies against BLV using agar gel immunodiffusion technique. The seropositivity rates of BLV, BHV1 and BVDV infections were 37.15%, 72.18% and 47.93% respectively. The BLV and BHV1 sero-prevalences significantly differed according to the age, the 2 year old animals being more resistant. Furthermore, significant interactions between the BLV and the 2 other viruses were evidenced by the chi-square method in the overall cow population and specifically in 4 dairy herds for the association of BLV with BHV1.
Keywords: BVDV; BHV1; BLV; cattle; serology; prevalence